Low-thermal-conductivity thermal barrier coatings with a multi-scale pore design and sintering resistance following thermal exposure - Zhang, Wei-Wei; Wei, Zhi-Yuan; Zhang, Li-Yuan; Xing, Ya-Zhe; Zhang, Qiang (Rare metals, 2020)
High-insulation, long-life thermal barrier coatings (TBCs) decrease the service temperature of superalloys and improve the service life of gas turbines. Improvement in the thermal insulation properties of the coating mainly depends on the optimization of the TBC structure. An important challenge for TBCs is maintaining a high performance during thermal exposure without degradation, as the pore-rich structure of the topcoat would inevitably be transformed by sintering. A low-thermal-conductivity anti-sintering coating can overcome the trade-off between thermal insulation and sinter degradation. In this review, the design, preparation, and serviceability evaluation of a low-thermal-conductivity anti-sintering coating will be discussed. Furthermore, directions for potential development are introduced. This paper provides a comprehensive understanding of the structured tailoring of TBCs for better thermal insulation and anti-sintering performance. Graphic abstract